Physical Activity, Biological Maturation and Bone Health as a Function of the Socio-Economic Status in Colombian Schools - Gómez-Rodas, Alejandro (2024)
Introduction: Several studies describe the different benefits of physical activity in children and adolescents. Indeed, when a deficit of physical activity is evident in these age groups, there is a concomitant increase in metabolic and metabolic disorders. Objective: to analyze the patterns of physical activity, biological maturation and bone mineral content in Colombian schoolchildren between 8 and 16 years of age according to the socioeconomic status to which they belong. Materials and methods: A quantitative, descriptive, cross-sectional study with a correlational scope, which included a representative sample of Colombian schoolchildren between 8 and 16 years of age, who were assessed for their level of physical activity through the PAQ-C, also, different anthropometric measurements are evaluated and indirectly the peak growth velocity (PSV) and bone mineral density (BMD) are prolonged. Results: a total of 2147 schoolchildren were evaluated, of which 56.7% belonged to educational institutions of the public system, statistically significant associations were found between sex and socioeconomic status with the level of physical activity and the other study variables. Conclusion: It can be concluded that physical activity, biological maturation and bone health are closely related to socioeconomic status in Colombian schoolchildren, which allows early diagnoses and decision-making regarding educational and public health programs and strategies.